Estresse hídrico em variedades tradicionais de feijão-caupi: estratégias fisiológicas e bioquímicas para tolerância ao déficit hídrico - Silva, Johny de souza (2019)
Cowpea bean is one of the most important sources of protein in the tropical and subtropical regions of the world. It is strategic in food security and has been generating employment and income, especially in the Brazilian Northeast. However, particularly in the northeastern semi-arid region, its cultivation is predominantly under rainfed conditions, in which rainfall irregularity and high temperatures have contributed to the water deficit, causing damage to the plants, which are often irreversible, with a consequent loss of productivity. The preference of many producers for the traditional / creole varieties may be due to their greater adaptation to the growing environment, which reduces the risk of total loss in production, increasing their chances of success in the semi-arid conditions. In many studies, the identification of tolerant genotypes is based on few variables related to drought responses. Thus, it is important to evaluate different physiological and biochemical variables that encompass several mechanisms to identify promising genotypes for cultivation in arid and semi-arid regions and, mainly, to try to elucidate the effects of this stress in different genetic materials. In this context, the present study sought to identify mechanisms of tolerance to water deficit in traditional varieties of cowpea cultivated in Ceará, through an integrated analysis involving physiological and biochemical variables that affect the growth and development of cowpea in a condition of water restriction, besides verifying the capacity of recovery after severe water deficit. Therefore, two experiments were carried out, the first in a completely randomized design in a 3x2x5 factorial scheme, where three genotypes were evaluated under two conditions (irrigated control and progressive dry for nine days), the other experiment was a 3x3x5 factorial scheme, where three genotypes and three water conditions (irrigated control, moderate stress and severe stress). Growth variables, water relations, carbon metabolism, osmotic adjustment and oxidative metabolism were evaluated. From the results obtained, it was possible to identify tolerance mechanisms in the different cowpea genotypes, expressed through the results of the physiological and biochemical evaluations, and, from this characterization, indicate genotypes with ability to cultivate in the rainforest, able to tolerate periods of soil water scarcity and with the capacity to recover from rehydration.